Challenges of professionals of vocational guidance: A look from the different labor contexts in Costa Rica (Costa Rican Journal of Guidance & Counseling, 2023)
Within the framework of the research Challenges of vocational guidance in various work contexts of Guidance professionals in Costa Rica, phase II, developed in 2021, this article highlights the challenges faced by guidance professionals from the different public work contexts, among these are: the National Institute of Learning; the Ministry of Public Education in I, II, III cycle and Diversified Education; the Ministry of Justice and Peace, the National Board of Children, and the State University System. The methodology of the study was developed under a naturalistic paradigm with a qualitative approach and a phenomenological analysis method, for the collection of information the interview technique was applied and a research workshop was developed. The information collected was organized and transcribed using the Atlas Ti program, which allows the triangulation of the data (interviews, the research workshop, and the theoretical conceptualization of each context), and the analysis of the information; finding among the main results, that the use of technological tools represents a challenge for the study population. On the other hand, there is a need for constant updating and learning about the various paradigms, approaches, and theories, specifically those related to the new trends in the discipline (including life design), as well as obtaining strategies to meet the current challenges of the 4.0 revolution, which are part of the challenges indicated by professionals in the discipline.
Keywords: Vocational orientation, challenges, challenges.